Blurring the Margins: Ardalén (2012) and Coleective Memory in Spain - Sarah Dibble Harris (Universitat Autònoma de Barcelona, 2017)
The title of Miguelanxo Prado’s Ardalén is a word invented by its author, but which refers to a real phenomenon: a long-distance wind that carries the scent of salt and sea far inland from the coast. In the fictional tale, this sea breeze carries with it not just air and smells, but also stories, as well as living sea creatures. Appropriate to its title, this winner of the 2012 National Spanish Comics Prize blurs lines between the real and the imaginary, between self and other, between land and sea, and between life and death. Blurry margins exist metaphorically in the book’s story as well as visually in its images, both within its panels and in its gutters. Drawing on Anne Whitehead’s recent discussion of modes of inscription and collective memory, this article explores the representation of memory and the fantastic in Miguelanxo Prado’s 2012 graphic novel Ardalén, noting the strong implications of Ardalén’s main character’s incapacity to distinguish between what he lived and what he heard in the context of the Recovery of Historical Memory in Spain’s early 21st century.